e#-open and *e-open sets via -open sets (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The notion of -open sets in a topological space was studied by Velicko.  Usha Parmeshwari et.al. and Indira et.al. introduced the concepts of b# and *b open sets respectively. Following this Ekici et. al. studied the notions of e-open and e-closed sets by mixing the closure, interior, -interior and -closure operators.  In this paper some new sets namely e#-open and *e-open sets are defined and their relationship with other similar concetps in topological spaces will be investigated.